COST ANALYSIS ON THE CONSTRUCTION OF SPORTS FACILITIES IN KEDEWAN SUB-DISTRICT, BOJONEGORO DISTRICT WITH EVM (EARNED VALUE METHOD) - Riduwan, Sanda Praja; Witjaksana, Budi; TJendani, Hanie Teki (INTERNATIONAL JOURNAL ON ADVANCED TECHNOLOGY, ENGINEERING, AND INFORMATION SYSTEM, 2023)
The implementation of construction work has the main targets in construction management, such as construction costs, quality of construction work and construction implementation time. Construction activities can be declared successful in their management if they produce work products with the quality criteria that have been determined, on time, and according to the agreed costs. Using EVM (Earned Value Method) in project management can be used to determine cost performance and implementation time during the project and the indicators used for analysis include: BCWP (Budget Cost of Work Performance), BCWS (Budget Cost of Work Schedule), ACWP (Actual Cost of Work Performance), SV (Schedule Variance), CV (Cost Variance), SPI (Schedule Performance Index), CPI (Cost Performance Index), EAS (Estimated At Schedule) and ETS (Estimated Temporary Schedule). By using this method in the Sports Facilities Construction Project, Kecamatan Kedewan, Kabupaten Bojonegoro, the ACWP (Actual Cost of Work Performed), BCWP (Budgeted Cost of Work Performed), and BCWS (Budgeted Cost of Scheduled) values were obtained. The CV value obtained <0 in weeks 1 to 7 indicates that the costs incurred were greater than the plan, but in weeks 8 to 15 the CV value >0 means that in that week the costs incurred were less than the plan. Meanwhile, meaning the project is experiencing a delay from plan. The estimated of the completion budget requirement obtained from the ETC (Estimate to Compile) value is Rp. 3,345,105,521.28, while the estimated final total project cost obtained from the EAC (Estimate at Complete) value is Rp. 5,680,868,593.22.